Perilaku Remaja Pengguna Facebook Berdasarkan Perspektif Gender - Widyastuti, Dhyah Ayu Retno; Santoso, Nobertus Ribut (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
The objective of this research was to understand the reality of teenagers in Yogyakarta using Facebook by using polling research design. Sample survey method was used to get the data from the respondents. The samples were 100 respondents who could represent the population. This research was conducted at SMA BOPKRI 2 Yogyakarta. The findings of the research were (1) High school teenagers both boys and girls have the same tendency in using internet; browsing to obtain the information in order to do their tasks and accessing social networks, (2) The trend in accessing social networks either boys or girls was Facebook, (3) Activity undertaken on Facebook either boys or girls was playing online game, (4) Both boys and girls used Facebook to interact with friends, (5) The media type used to access the internet was a laptop. However, if it was seen from media ownership to access internet, mobile phone was higher than laptop, (6) In term of the place to access internet, boys tend to access the internet at home whereas girls tend to access tinternet at school. The findings showed, based on the sex, the trend of using Internet between boy and girl was equal. Based on gender perspective, the reality of internet usage provides equal opportunities for boys and girls to access the facilities that were available on internet.